A chloride efflux transporter, BIG RICE GRAIN 1, is involved in mediating grain size and salt tolerance in rice. Issue 12 (18th November 2021) - Ren, Zhijie; Bai, Fenglin; Xu, Jingwen; Wang, Li; Wang, Xiaohan; Zhang, Qian; Feng, Changxin; Niu, Qi; Zhang, Liying; Song, Jiali; Bao, Fang; Liu, Liangyu; et al.
Abstract: Grain size is determined by the size and number of cells in the grain. The regulation of grain size is crucial for improving crop yield; however, the genes and molecular mechanisms that control grain size remain elusive. Here, we report that a member of the detoxification efflux carrier /Multidrug and Toxic Compound Extrusion (DTX/MATE) family transporters, BI G R ICE G RAIN 1 (BIRG1), negatively influences grain size in rice ( Oryza sativa L.). BIRG1 is highly expressed in reproductive organs and roots. In birg1 grain, the outer parenchyma layer cells of spikelet hulls are larger than in wild‐type (WT) grains, but the cell number is unaltered. When expressed in Xenopus laevis oocytes, BIRG1 exhibits chloride efflux activity. Consistent with this role of BIRG1, the birg1 mutant shows reduced tolerance to salt stress at a toxic chloride level. Moreover, grains from birg1 plants contain a higher level of chloride than those of WT plants when grown under normal paddy field conditions, and the roots of birg1 accumulate more chloride than those of WT under saline conditions. Collectively, the data suggest that BIRG1 in rice functions as a chloride efflux transporter that is involved in mediating grain size and salt tolerance by controlling chloride homeostasis. Abstract : The rice detoxification efflux carrier/Multidrug and Toxic Compound Extrusion (DTX/MATE) family transporter B IG R ICE G RAIN 1 mediates chloride efflux, thus negatively influencing grain size and salt tolerance by controlling chloride homeostasis.